Roughness of human enamel surface submitted to different prophylaxis methods - Castanho, Gisela Muassab; Arana-Chavez, Victor E.; Fava, Marcelo [UNESP] (MRE Press, 2008)
The purpose of this in vitro study was to evaluate alterations in the surface roughness and micromorphology of human enamel submitted to three prophylaxis methods. Sixty-nine caries-free molars with exposed labial surfaces were divided into three groups. Group I was treated with a rotary instrument set at a low speed, rubber cup and a mixture of water and pumice; group II with a rotary instrument set at a low speed, rubber cup and prophylaxis paste Herjos-F (Vigodent S/A Indústria e Comércio, Rio de Janeiro, Brazil); and group III with sodium bicarbonate spray Profi II Ceramic (Dabi Atlante Indústrias Médico Odontológicas Ltda, Ribeirão Preto, Brazil). All procedures were performed by the same operator for 10 s, and samples were rinsed and stored in distilled water. Pre and post-treatment surface evaluation was completed using a surface profilometer (Perthometer S8P, Mark, Perthen, Germany) in 54 samples. In addition, the other samples were coated with gold and examined in a scanning electron microscope (SEM). The results of this study were statistically analyzed with the paired t-test (Student), the Kruskal-Wallis test and the Dunn (5%) test. The sodium bicarbonate spray led to significantly rougher surfaces than the pumice paste. The use of prophylaxis paste showed no statistically significant difference when compared with the other methods. Based on SEM analysis, the sodium bicarbonate spray presented an irregular surface with granular material and erosions. Based on this study, it can be concluded that there was an increased enamel surface roughness when teeth were treated with sodium bicarbonate spray when compared with teeth treated with pumice paste.
Keywords: Dental enamel; Dental prophylaxis; Enamel roughness; Jet abrasive system; Scanning electron microscope